Guidance & Counseling Programs: Coping With Student School Burnout - Sari, Ari Novita (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
School burnout is a physical, mental and emotional depression experienced by students as a result of the demands of school and educational life. Caused by several factors, namely: loss of interest in school, study fatigue, family fatigue, homework fatigue, etc. This study uses a quantitative method using the SBI instrument for grade 7th junior high school students. The purpose of this study was to analyze the condition of school burnout for grade 7 students. The results showed that most of the school burnout experienced by students was in the moderate category. However, after further investigation, the school burnout experienced by students was in the high category for indicators of burnout on schoolwork, feelings of inadequacy at school, and burnout from problems that developed at school. Several programs are provided to overcome this problem e through basic services and responsive services by GC teachers. This service is intended to help students have a positive attitude towards the future and build students' subjective well-being